Contemporary Canadian Federalism : Foundations, Traditions, Institutions - Gagnon, Alain (Book collections on Project MUSE., 2009)
Filled with stimulating work that bridges the gap between distinctive traditions in English- and French-Canadian scholarship on federalism, this important volume is required reading for understanding provincial-federal relations and Canadian governance.